A Study on Nurses' Perspectives of Work Schedules - Miray Aksu; Leyla Dinc (Association of Nurse Managers, 2023)
Aim: This descriptive study was conducted to analyze the existing situation and nurses' perspectives on work schedules. Method: The study sample consisted of 207 nurses who worked at 23 state hospitals. The data were collected with a 40-item questionnaire developed by the researchers. Descriptive statistics, Kruskal-Wallis, Mann-Whitney U, chi-square, and Spearman's correlation tests were used for data analysis. Results: The mean numbers of beds, nurses, daily hospitalized patients, and patients in the unit on the last shift were 24.23 (SD=15.01), 14.79 (SD=10.48), 9.16 (SD=8.2), and 12.10 (SD=10.28), respectively. Of the nurses, 49% had a rotating shift, 54.8% were dissatisfied with the shift system, and nurse scheduling was mostly prepared on paper by the clinic's responsible nurses and then loaded onto a computer. Conclusion: Fair and objective criteria and software should be used to prepare schedules with mostly fixed shifts and convenient work hours, without wasting time on manual scheduling. These results indicate factors that need to be taken into consideration in the preparation of nurses' work schedules and workforce planning.